Vocational Education in Higher Secondary Schools: A Review of Factors Influencing Student Interest and Attitudes - Saroj Mahale; Varsha Tripathi (International Journal of Education Sciences, 2025)
The study investigates the essential aspects influencing students' motivation and attitudes toward vocational education in higher secondary schools, emphasizing its changing importance in current educational systems. Vocational education, which focuses on hands-on training and real-world applications, is critical in closing the gap between academic learning and the labor market. Despite its promise to promote employment, diversity, and economic development, vocational education faces considerable obstacles, such as societal stigma, insufficient resources, and misaligned curricula. The report also looks at techniques for increasing student engagement, including as using current technologies, matching programs with student objectives and industry needs, and creating inclusive learning environments. The study emphasizes the role of government policy and business collaboration in making vocational education a viable, valued, and beneficial educational pathway. The study also emphasizes how crucial professional development and teacher training are to raising the caliber and relevance of instruction. It emphasizes the necessity of awareness-raising initiatives to change public opinion and inspire community and parental support. The study provides useful suggestions for educators, legislators, and stakeholders looking to improve the efficacy and appeal of vocational education for upcoming generations by identifying the main drivers and obstacles.
Keywords: Vocational education; educational inclusivity; government policies; labour market alignment; skill development; student engagement